2019
DOI: 10.1016/j.cell.2019.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Primate Amygdala Neurons Simulate Decision Processes of Social Partners

Abstract: Summary By observing their social partners, primates learn about reward values of objects. Here, we show that monkeys’ amygdala neurons derive object values from observation and use these values to simulate a partner monkey’s decision process. While monkeys alternated making reward-based choices, amygdala neurons encoded object-specific values learned from observation. Dynamic activities converted these values to representations of the recorded monkey’s own choices. Surprisingly, the same activity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 57 publications
2
98
0
Order By: Relevance
“…Neither the fine grain single unit literature nor the coarser neuroimaging literature brought conclusive evidence for or against the functional compartmentalization of the primate amygdala. Only a small fraction of the single unit studies reported an uneven distribution of neurons with particular response properties across the nuclei (e.g., Clayton P Mosher, Zimmerman, and Gothard 2010; Zhang et al 2013;Grabenhorst et al 2019). To complicate things further, an increasing number of single unit studies reported that neurons in the amygdala respond to multiple stimulus dimensions and task parameters (Saez et al 2015;Kyriazi, Headley, and Pare 2018b;Munuera, Rigotti, and Salzman 2018;Morrow, Mosher, and Gothard 2019;Putnam and Gothard 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Neither the fine grain single unit literature nor the coarser neuroimaging literature brought conclusive evidence for or against the functional compartmentalization of the primate amygdala. Only a small fraction of the single unit studies reported an uneven distribution of neurons with particular response properties across the nuclei (e.g., Clayton P Mosher, Zimmerman, and Gothard 2010; Zhang et al 2013;Grabenhorst et al 2019). To complicate things further, an increasing number of single unit studies reported that neurons in the amygdala respond to multiple stimulus dimensions and task parameters (Saez et al 2015;Kyriazi, Headley, and Pare 2018b;Munuera, Rigotti, and Salzman 2018;Morrow, Mosher, and Gothard 2019;Putnam and Gothard 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These neurons have previously been shown to have properties resembling ‘mirror’ neurons 34-37 , but their role in the cultural transmission of vocal behaviors was not well understood. The functional significance of mirror neurons in behavioral imitation and ASD is a topic of much debate 38-43 . We show that knockdown of FoxP1 in striatal projecting HVC X neurons clamps their spine plasticity, dampens their intrinsic excitability, and blocks the cellular and network level signatures associated with tutor-song memory formation following social experience.…”
Section: Discussionmentioning
confidence: 99%
“…This limits our ability to guess what information might be passing between the frontal and temporal regions. Yet, there is an increasing number of studies examining social behaviour between more than one subject (Grabenhorst, Báez-Mendoza, Genest, Deco, & Schultz, 2019;Haroush & Williams, 2015;K. Yoshida et al, 2012), so it is becoming more feasible to conduct experiments involving two or more monkeys interacting with one another.…”
Section: Future Directionsmentioning
confidence: 99%